A Culture-Based Pedagogical Approach: Exploring the Role of Keraton Sumenep's Andhāp Asor in Fostering Pancasila Character among Fourth-Grade Students - Asri Istiqomaturrobiah; Ahmad Sudi Pratikno (Jurnal Elementaria Edukasia, 2026)
This study aims to examine in depth the role of Andhāp Asor values, which originate from the culture of the Keraton Sumenep, in shaping the Pancasila character of fourth-grade elementary school students. Through a culture-based pedagogical approach and exploratory methods, this study was conducted at elementary school of Daramista II, focusing on how elements of local culture can be integrated into the learning process to strengthen students' moral and social character. The main issue examined in this study is how the noble values of Andhāp Asor, such as humility, respect, politeness, and courtesy, can be internalized in learning activities as part of efforts to build Pancasila character. This study used an exploratory qualitative approach, with data collection techniques in the form of field observations, interviews with teachers, students, and cultural figures from the Keraton Sumenep, as well as documentation. The findings show that the cultural values of Andhāp Asor are still alive and practiced in the life of the Keraton Sumenep and have a strong connection with the values of Pancasila, especially in the aspects of humanity, social justice, and harmony in society. The application of Andhāp Asor values in the classroom is able to foster mutual respect, cooperation, and polite communication among students. Based on this, it can be said that the application of a culture-based pedagogical approach through the exploration of Andhāp Asor values can support the strengthening of Pancasila character education and raise students' awareness and pride in their local culture.